Thermal-Electrochemical Co-drive System for Carbon Capture. (July 2017) - Liu, G.X.; Yu, Y.S.
Abstract: Cost-effective and large-scale carbon dioxide capture system is a critical technology for greenhouse gas abatement. However, current capture technologies are energy and capital intensive, which prohibits the deployment in power plants. Particularly, the need for elevated temperature steam is a troublesome problem for plants. In this work, we proposed a technology of Thermal-Electrochemical Co-drive System (TECS), which integrates electrochemical process and benign thermal process, as the solution of the above-mentioned problems. Since the fact that the binding site of metal-amine is identical with that of carbon dioxide (CO2 )-amine, CO2 can be released easily. TECS is a technology based on coordination reactions, utilizing electrochemical method and thermodynamic principle to desorb CO2 and regenerate amine. In addition, experiments study on TECS based on Cu(II) and monoethanolamine (MEA) was conducted. Results of CO2 capacity of MEA aqueous solutions added Cu(II) suggest that Cu(II) shows strong inhibitory effects on the absorption process. In addition, the electrochemical impedance spectroscopy (EIS) was measured at different polarization potentials.